2021
DOI: 10.1155/2021/5561672
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive Compounds of Raspberry Oil Emulsions Induced Oxidative Stress via Stimulating the Accumulation of Reactive Oxygen Species and NO in Cancer Cells

Abstract: There are growing interests in the complex combinations of natural compounds that may advance the therapy of cancer. Such combinations already exist in foods, and a good representative is seed oils. Two raspberry oils: cold pressed (ROCOP) and one extracted by supercritical CO2 (ROSCO2) were evaluated for their chemical characteristics and oil emulsions for cell suppression potential against colon adenocarcinoma (LoVo), doxorubicin-resistant colon adenocarcinoma (LoVo/DX), breast cancer (MCF7), doxorubicin-res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 44 publications
(67 reference statements)
2
13
1
Order By: Relevance
“…Especially, the M line oil contained significantly more polyphenols. As we have shown in our previous studies, the subtle differences in composition of the minor bioactives in oils may result in diverse effectiveness in normal and cancer cells [ 24 , 25 ]. The observed inhibitory impact of B oil on neoplastic cell proliferation could be partially attributed to its marginally elevated stigmasterol concentration compared to the other examined oils.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Especially, the M line oil contained significantly more polyphenols. As we have shown in our previous studies, the subtle differences in composition of the minor bioactives in oils may result in diverse effectiveness in normal and cancer cells [ 24 , 25 ]. The observed inhibitory impact of B oil on neoplastic cell proliferation could be partially attributed to its marginally elevated stigmasterol concentration compared to the other examined oils.…”
Section: Discussionmentioning
confidence: 99%
“…Flaxseed oils were tested at final concentrations of 0.1 mg, 0.25 mg, 0.5 mg, 1.0 mg, and 2.5 mg per 1 mL of the medium at room temperature and in sterile conditions. The range of concentrations of the tested oils used is not toxic to cells and allows for chemopreventive effects in cancer cell model [ 25 ]. The MB oil emulsions were prepared by mixing 1:1 B and M oil ( v / v ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Grazjer et al have studied two raspberry oils (0.5–10%): cold-pressed and extracted by supercritical CO 2 . They have observed that both tested oils are good candidates for non-toxic support in the therapy of selected human cancers, including colon adenocarcinoma (LoVo), breast cancer (MCF7), and lung cancer (A549) cell lines [ 41 ].…”
Section: Health-promoting Properties Of Berry Seeds—in Vitro and In V...mentioning
confidence: 99%
“…Oxygenic compounds [28][29][30] in biomass thermal electrolyte mainly contain carboxyl, base, and hydroxyl groups, and the reduction of oxygenic compounds is mainly due to the removal reaction of these three groups. 1), mainly the fracture of -COOH bond, mainly organic acids, including acetic acid, oleic acid, and palmitate, which will produce methane or ethylene; oleic acid and palmitate are usually saturated alkane.…”
Section: Fractions Of the Reforming Fluidmentioning
confidence: 99%